Plasmonic Logic Gates at Optimum Optical Communications Wavelength - Z. S. Al-Sabea; A. A. Ibrahim; S. H. Abdulnabi (Advanced Electromagnetics, 2022)
This paper displays a design that realizes all optical logic gates (NOT, AND, OR, NAND, NOR, XOR, XNOR) and consisting of one nanoring and four strips Operates on the principle of resonance. the proposed design works at the wavelength of 1550 nm using insulator-metal-insulator (IMI) plasmonic waveguide. The basic principle of the operation of these gates is input and control signals’ constructive and destructive interference. The proposed transmission threshold’s value is 0.25 between OFF state and ON state. The proposed design has small dimensions (300 nm × 300 nm) and can realize seven logic gates with maximum transmission 134% at NOT gate, 223% at OR gate, 134% at NAND gate and 223% at XNOR gate where the design is optimum and excellent design and the modulation depth is very high because it’s ranges in all gates more than 90%. The proposed structure contributes in building nanocircuits for integrated photonic circuits and optical signal processing.